Letter from Carl D. Duncan to Patricia Whiting, April 26, 1966 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
Duncan discusses a concert performed by John Cage and expresses his appreciation of Whiting's friendship, and provides his itinerary for his travel to Bloomington, Indiana.